DEVELOPING THE ABILITIES OF PEOPLE WITH DISABILITIES THROUGH INNOVATIVE PEDAGOGICAL APPROACHES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the role of innovative pedagogical approaches in enhancing the abilities and potential of persons with disabilities within the context of inclusive education and social integration. The study emphasizes that the effective application of learner-centered teaching strategies, adaptive learning technologies, and competency-based assessment systems contributes significantly to the intellectual, professional, and social development of individuals with special needs. It is highlighted that inclusive education practices, supported by digital platforms, interactive teaching methods, and individualized curricula, play a decisive role in expanding equal opportunities for learning and professional growth. Moreover, the article analyzes the importance of teacher training, digital literacy, and the creation of a supportive educational environment in ensuring active participation of persons with disabilities in lifelong learning and the labor market. The findings underline that innovative pedagogical approaches not only facilitate the realization of personal abilities but also contribute to the development of human capital and the strengthening of social justice principles in modern society.